Effectiveness of the use of vaccines in the schemes of preventive measures regarding infectious rhinotracheitis in cats in the conditions of the veterinary clinic “Aybolit” in the city of Kharkiv - Ruban, V.; Severin, R.; Gontar’, A.; Ponomarenko, G. (Scientific Progress & Innovations, 2022)
Infectious rhinotracheitis, as a herpesvirus infection, is very common among cats and is manifested in an acute course by damage to the eyes and respiratory organs. Despite significant scientific developments in the diagnosis and treatment of sick animals, the issue of choosing effective means of specific prevention remains relevant. The aim of the research was to find out the effectiveness of various vaccines from leading manufacturers against infectious rhinotracheitis in cats. To achieve the goal, the following tasks were solved, such as the study of the spread of the disease, the peculiarities of seasonality, and age susceptibility. The research was carried out in the conditions of a private veterinary clinic in Kharkiv in 2020–2021. It was found out that the incidence of herpes virus infection in cats was 25.8 %. Seasonal fluctuations in infectious rhinotracheitis were determined in the spring-autumn period with the largest number of cases in October-November (28.0 %) and in March-April (31.0 %). Analysis of age dynamics showed that cats are most susceptible to herpes virus infection at the age of 10 weeks (23.0 %) and at the age of 12 weeks (20.5 %), minimally susceptible to the disease at the age of 3 years and older (2.5 %). Cases of the disease were also registered among cats 6 years of age and older (15.3 %). The results of the analysis of epizootological indicators regarding infectious rhinotracheitis of cats indicate its significant spread in the conditions of the city of Kharkiv and require the scientifically based application of effective specific means. As a result of the study of the effectiveness of various vaccines of leading manufacturers against infectious rhinotracheitis in cats, the drugs of choice were the vaccines “Nobivak TRICAT Trio” and “Zoetis Felocell 4”, which provided 100 % effectiveness when administered to kittens at the age of 9–12 weeks. Vaccines “PureVaxRCPCH” and “Feligen CRP” when administered to kittens at 8 weeks of age showed the effectiveness of 86.0 % and 71.0 %, respectively. In order to improve the efficiency of the use of vaccines, it is necessary to regularly introduce monitoring studies with the isolation of circulating strains of the virus in a certain region in order to analyze their compatibility with the composition of vaccine antigens. An important issue remains to clarify the level of general resistance and colostral immunity of susceptible young animals before the introduction of vaccination.